Efficient heat integration of industrial CO2 capture and district heating supply - Eliasson, Åsa; Fahrman, Elin; Biermann, Max; Normann, Fredrik; Harvey, Simon (International Journal of Greenhouse Gas Control, 2022)
Excess heat from industrial processes can be used for carbon capture and storage (CCS) as well as providing heat to a district heating network, leading to increased energy efficiency and reduction of on-site and/or off-site CO2 emissions. In this work, both options are assessed with respect to economic performance and potential reduction of CO2 emissions. The work includes a generic study based on five heat load curves for each of which three CO2 capture plant configurations were evaluated. The economic assessment indicates that the specific cost of capture ranges from 47-134 €/t CO2 depending on heat profile and capture plant configuration. Having excess heat available during a long period of the year, or having a high peak amount of heat, were shown to lead to low specific capture costs. The paper also includes results of a case study in which the methodology was applied to actual seasonal variations of excess heat for an integrated steel mill located in northern Sweden. Specific capture costs were estimated to 27-44 €/t CO2, and a 36% reduction of direct plant emissions can be achieved if the CO2 capture plant is prioritized for usage of the available excess heat